2019
DOI: 10.15243/jdmlm.2019.071.1959
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tillage systems and dosages of cow manure on weed and soybeans yield (Glycine max, Merrill)

Abstract: A field experiment to elucidate the effect of tillage systems and dosages of cow manure on weed and soybeans yield (Glycine max, Merrill) was conducted at the Agrotechno Park of the University of Brawijaya in Jatikerto, Malang, from May to July 2017. The experiment used a split-plot design with 3 replications. The main plot was the tillage systems, with 3 levels: T0= No-tillage, T1= Minimum tillage, and T2 = Conventional tillage. The subplot was the dosages of cow manure, with 3 levels: P1= 2.5 t cow manure/ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Sebayang and Rifai [18], on the other hand, found that the dry weed weight in the soybean crop did not differ significantly between conventional tillage, reduced tillage, and no-tillage. Nonetheless, many authors point out that the no-tillage system increases weed infestation of crops [29][30][31][32]. Our experiment also demonstrated a significant increase in the number and weight of weeds under the NT system in comparison with CT.…”
Section: Discussionsupporting
confidence: 62%
“…Sebayang and Rifai [18], on the other hand, found that the dry weed weight in the soybean crop did not differ significantly between conventional tillage, reduced tillage, and no-tillage. Nonetheless, many authors point out that the no-tillage system increases weed infestation of crops [29][30][31][32]. Our experiment also demonstrated a significant increase in the number and weight of weeds under the NT system in comparison with CT.…”
Section: Discussionsupporting
confidence: 62%
“…Cow manure gave the highest results on the number of seeds (85.58±27.40), which was significantly different from the control, and increased the number of seeds by about 29.33% (Table 3). Cow manure was reported to have a significant effect on the total weight of seeds, the weight of 100 seeds, and the productivity of the plants (Sebayang and Fatimah, 2019). This is because cow manure has a high content of nitrogen and phosphorus in the soil (Ghedabna et al, 2022).…”
Section: Soybean Yieldmentioning
confidence: 99%
“…Weed infestation in a crop field is determined by habitat factors and agronomic practices as well as by cultivar properties [Gawęda et al 2015, Sebayang and Rifai 2018, Sebayang and Fatimah 2019, Chojnacka and Haliniarz 2020, Gawęda et al 2020]. Individual cultivars differ not only in their type of use, earliness group, and sensitivity to diseases, but also in their competitiveness against weeds which results, among others, from different rates of initial growth [Shawon et al 2018, Marín 2021.…”
Section: Introductionmentioning
confidence: 99%